Scientific and Technological Interventions for Attaining Precision in Plant Genetics and Breeding - Narain Prem (Journal of Agronomy Research, 2018)
The scientific and technological interventions for attaining precision in plant genetics and breeding since Mendel’s discovery of genetic laws have been critically reviewed in terms of cloning technology and reverse genetics, chip technology, genetically modified organisms and CRISPR-based gene editing technology. Their roles in further refining the plant genetics and breeding practices particularly their exploitation in creating variations and their use for development of superior genotypes in model crops like wheat and rice have been discussed. It is stressed how such interventions could prove to be promising for meeting future crop improvement program in terms of climate change, bio-fortification, imaging technology, statistics, big data revolution and deep learning.
Keywords: Plant genetics and breeding